2015
DOI: 10.1111/jvh.12392
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus infection: a risk factor for Parkinson's disease

Abstract: Recent studies found that hepatitis C virus (HCV) may invade the central nervous system, and both HCV and Parkinson's disease (PD) have in common the overexpression of inflammatory biomarkers. We analysed data from a community-based integrated screening programme based on a total of 62,276 subjects. We used logistic regression models to investigate association between HCV infection and PD. The neurotoxicity of HCV was evaluated in the midbrain neuron-glia coculture system in rats. The cytokine/chemokine array … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
82
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(85 citation statements)
references
References 36 publications
1
82
1
1
Order By: Relevance
“…A number of epidemiological studies have reported an increased risk of PD risk following various types of infections and inflammation, including hepatitis C, herpes viruses, influenza, and H. pylori . Interestingly, both vagotomy studies reported an increased PD risk (HR = ∼1.1‐1.2) among the selective/super‐selective vagotomy patients compared to the background population.…”
Section: Protective Effect Of Vagotomymentioning
confidence: 99%
“…A number of epidemiological studies have reported an increased risk of PD risk following various types of infections and inflammation, including hepatitis C, herpes viruses, influenza, and H. pylori . Interestingly, both vagotomy studies reported an increased PD risk (HR = ∼1.1‐1.2) among the selective/super‐selective vagotomy patients compared to the background population.…”
Section: Protective Effect Of Vagotomymentioning
confidence: 99%
“…The association between the Hepatitis C virus infection and risk of PD has been the subject of a recent review, evaluating three large retrospective cohort studies including two nationwide studies and one case control study, with all studies consistently showing an increased risk for PD . Findings from studies in the East have shown an association between only Hepatitis C infection and PD; whereas one retrospective cohort study from the UK found an association between the Hepatitis B and C virus infection with PD, but not with other forms of hepatitis . Large nationwide health‐insurance database and large regional screening programs for Hepatitis, implemented in Taiwan, have enabled this previously unknown association between the Hepatitis C virus and PD to be described, findings of which have been recently replicated in the West in a nationwide UK study, utiliaing the UK HES database…”
Section: Analytical Epidemiologymentioning
confidence: 99%
“…Mechanisms proposed for the association include, direct Hepatitis C virus infection of the brain and interferon induced Parkinsonism. The Hepatitis C virus has been shown in mouse models to induce neuronal toxicity similar to that of 1‐methyl‐4‐phenylpyridinium (MPP+) . Prospective cohort studies have yet to be performed and further studies are necessary to clarify the potential contributory role of interferon treatment and PD, which has been reported in isolated case reports to induce parkinsonism.…”
Section: Analytical Epidemiologymentioning
confidence: 99%
“…Further, it interferes with the function of neurons and their homeostasis of the nervous system, leading to the generation of neuronal damage and neurodegeneration (De Chiara et al, 2012). The infective agents affect the neurological system and cause neurodegenerative diseases such as AD, PD, and ALS (Alkhawajah et al, 2015;Bourgade et al, 2015;DeVaughn et al, 2015;Wu et al, 2015b). Further, progressive infective neurodegeneration occurs with a wide range of molecular and cellular mechanisms leading to deterioration or loss of neurons in the CNS.…”
Section: Neuroinfection-associated Neurodegenerative Diseasementioning
confidence: 99%